(untitled) (GYMNASIUM, 2008)
In the past years, the International Federation of Amateur Fight Associations has done some modifications in the challenge rules. These modifications convicted the specialists in the domain to conclude that the investigation of the ways for improving the results must be directed onto enlargement of technical skill. A perfect technique, dubbed by a rich technical diversity is what always marked the Romanian fighting school.